Mindfulness beyond secularization: Beliefs across meditators and non-meditators reflect a consensus on personal development over health and spirituality - Philippine Chachignon; Emmanuelle Le Barbenchon; Cécile Dantzer; Lionel Dany (PLoS ONE, 2025)
Background Mindfulness meditation (MM), originating from spiritual traditions but widely promoted as a secular and beneficial practice, is increasingly debated due to potential adverse effects, ethical concerns, and its ties with neoliberal imperatives, challenging its image as a universal remedy. Beliefs about MM strongly influence its reception, usage, and effects but remain understudied, especially in comparing meditators and non-meditators. Understanding these beliefs is key to clarifying how lay perceptions align or diverge from scientific frameworks and to grasp individuals’ expectations and motivations, notably in clinical contexts. Existing research often overlooks belief content or comparisons between meditators and non-meditators. Objective This study explored the content of beliefs about MM, identified missing elements, and compared meditators’ and non-meditators’ beliefs. Associations with sociodemographic, motivational, health, and psychological variables were examined. Methods 167 participants (105 meditators) completed an online survey producing five words linked to MM, rated for valence, plus questionnaires on motivation, beliefs, and personal characteristics. Results 817 free associations were collected; 65% were positive. Hierarchical classification identified five belief categories: “Body-based Relaxation,” “Stereotyped Descriptions,” “Psychological and Affective Well-Being,” “Focus on Inner-Self,” and “Experience of MM.” Four categories were shared by both groups, with meditators showing more precise, experiential understanding. Beliefs varied with sociodemographic, health, and psychological factors. Core aspects in MM like attention, acceptance, health, collective dynamics and ethical concerns were largely absent. Notably, spirituality was not integrated into the beliefs about MM. Conclusions Findings emphasize MM as a self-regulatory and personal development tool shaped by social, psychological and behavioural factors. Recognizing both current and potential MM users’ beliefs can improve tailoring of mindfulness interventions and encourage instructors to address ethical and adverse aspects openly, fostering more informed, responsible practice.